Social Aspects of New Technologies - the CCTV and Biometric (Framing Privacy and Data Protection) in the Case of Poland; Społeczne aspekty nowych technologii - CCTV i biometrii (koncepcja prywatnosći i ochrony danych osobowych) na przykładzie Polski - Zofia Wysokinska; Radosław Dziuba (Comparative Economic Research. Central and Eastern Europe, 2011)
The purpose of this paper is to review the institution responsible for the protection of personal data within the European Union and national example - Polish as a country representing the new Member States. The analysis of institutional system - providing legal security of communication and information institutions, companies and citizens against the dangers arising from the ongoing development of innovative new technologies in the European Union and Poland. This article is an attempt to analyze the possibility of using security systems and Biometry CTTV in Poland in terms of legislation. The results of the analysis indicate that, in terms of institutions Poland did not do badly in relation to the risks arising from the implementation of technology. The situation is not as good when it comes to the awareness of citizens and small businesses. This requires that facilitate greater access to free security software companies from data leakage or uncontrolled cyber-terrorist attacks. With regard to the use of security systems, CCTV and biometrics, Poland in legal terms is still early in the process of adapting to EU Directive. The continuous development of technology should force the legislature to establish clear standards and regulations for the application of CCTV technology and biometrics, as it is of great importance in ensuring the fundamental rights and freedoms of every citizen of the Polish Republic. – – Celem niniejszego artykułu jest przeglad instytucji odpowiadajacych za ochrone danych osobowych na poziomie Unii Europejskiej oraz na przykładzie narodowym - Polski jako kraju reprezentujacego nowe panśtwa członkowskie. Przedmiotem analizy jest system instytucjonalno - prawny zapewniajacy bezpieczenśtwo komunikacyjne oraz informacyjne instytucji, przedsiebiorstw jak i obywateli przed zagrozėniami wynikajacymi z innowacyjnych rozwiazanṕostepujacego rozwoju nowych technologii zaroẃno w Unii Europejskiej jak i w Polsce. Ponizṡzy artykuł jest roẃniezṗrob́a analizy mozl̇iwosći stosowania systemoẃ zabezpieczenĆTTV oraz Biometrii w Polsce w ujeciu prawnym. Wyniki analizy wskazuja, zė pod wzgledem instytucji Polska nie wypada zĺe w odniesieniu do zagrozėnẃynikajacych z wdrozėnia technologii. Sytuacja nie jest tak dobra, jesĺi chodzi o sẃiadomosćóbywateli i mniejszych firm. Wymaga to ułatwiania szerszego dostepu do darmowych programoẃ zabezpieczajacych firmy przed wyciekiem danych lub niekontrolowanych cyber-atakoẃ terrorystycznych. W odniesieniu do stosowania systemoẃ zabezpieczenĆCTV oraz biometrii, Polska pod wzgledem prawnym jest wciazṅa poczatku procesu dostosowania do dyrektywy UE. Ciagły rozwoj́ technologii powinien zmusicústawodawce do stworzenia jednoznacznych standardoẃ i przepisoẃ obowiazujacych w zakresie stosowania technologii CCTV oraz biometrii, gdyzṁa to ogromne znaczenie w zapewnieniu podstawowych praw i wolnosći kazḋego obywatela Rzeczypospolitej Polskiej.
Keywords: 330